Acute and midterm outcomes of the post-approval MELODY Registry: a multicentre registry of transcatheter pulmonary valve implantation. (21st April 2019) - Nordmeyer, Johannes; Ewert, Peter; Gewillig, Marc; AlJufan, Mansour; Carminati, Mario; Kretschmar, Oliver; Uebing, Anselm; Dähnert, Ingo; Röhle, Robert; Schneider, Heike; Witsenburg, Maarten; Benson, Lee; et al.
Abstract: Aims: The post-approval MELODY Registry aimed to obtain multicentre registry data after transcatheter pulmonary valve implantation (TPVI) with the Melody™ valve (Medtronic plc.) in a large-scale cohort of patients with congenital heart disease (CHD). Methods and results: Retrospective analysis of multicentre registry data after TPVI with the Melody™ valve. Eight hundred and forty-five patients (mean age: 21.0 ± 11.1 years) underwent TPVI in 42 centres between December 2006 and September 2013 and were followed-up for a median of 5.9 years (range: 0–11.0 years). The composite endpoint of TPVI-related events during follow-up (i.e. death, reoperation, or reintervention >48 h after TPVI) showed an incidence rate of 4.2% per person per year [95% confidence interval (CI) 3.7–4.9]. Transcatheter pulmonary valve implantation infective endocarditis (I.E.) showed an incidence rate of 2.3% per person per year (95% CI 1.9–2.8) and resulted in significant morbidity and in nine deaths. In multivariable Cox proportional hazard models, the invasively measured residual right ventricle (RV)-to-pulmonary artery (PA) pressure gradient (per 5 mmHg) was associated with the risk of the composite endpoint (adjusted hazard ratio: 1.21, 95% CI 1.12–1.30; P  <   0.0001) and the risk of TPVI I.E. (adjusted hazard ratio: 1.19, 95% CI 1.07–1.32; P  =   0.002). Major procedural complications (death, surgical, or interventional treatment requirement) occurred in 0.5%, 1.2%, and 2.0%, respectively. Acutely, the RV-to-PA pressure gradient and the percentage of patients with pulmonary regurgitation grade >2 improved significantly from 36 [interquartile range (IQR) 24–47] to 12 (IQR 7–17) mmHg and 47 to 1%, respectively ( P  <   0.001 for each). Conclusion: The post-approval MELODY Registry confirms the efficacy of TPVI with the Melody™ valve in a large-scale cohort of CHD patients. The residual invasively measured RV-to-PA pressure gradient may serve as a target for further improvement in the composite endpoint and TPVI I.E. However, TPVI I.E. remains a significant concern causing significant morbidity and mortality.